Conceptualizing the Influence of Social Agents of Behavior Change A Meta-Analysis of the Effectiveness of HIV-Prevention Interventionists for Different Groups. [article].
A meta-analysis of 166 HIV-prevention interventions tested theoretical predictions about the effects of experts, lay community members, and similar and dissimilar others, as agents of change. In general--, expert interventionists produced greater behavior change than lay community members, and the demographic and behavioral similarity between the interventionists and the recipients facilitated behavioral change. Equally, importantly there were differences across groups in the efficacy of various sources, especially among populations of low status and/or power. These findings support the hypothesis that unempowered populations are more sensitive to characteristics of the interventionists who can facilitate access to various sources. In addition, they suggest the need to ensure the availability of health professionals from diverse demographic and behavioral bacgrounds. -- (from the author)
Keywords: HIV prevention; Source features effect; Similarities; Source-audience effect